make the setoid parameter to sequenceV-cong explicit
authorHelmut Grohne <helmut@subdivi.de>
Sun, 25 Nov 2018 09:59:34 +0000 (10:59 +0100)
committerHelmut Grohne <helmut@subdivi.de>
Sun, 25 Nov 2018 09:59:34 +0000 (10:59 +0100)
Later versions of agda will be unable to infer it unambiguously.

Bidir.agda

index c4c2f60..348e60b 100644 (file)
@@ -231,17 +231,17 @@ module _ (G : Get) where
       ≡⟨ P.cong (sequenceView ∘ get) (P.sym (lemma-sequence-successful SourceShapeT v p)) ⟩
     sequenceView (get v) ∎
 
       ≡⟨ P.cong (sequenceView ∘ get) (P.sym (lemma-sequence-successful SourceShapeT v p)) ⟩
     sequenceView (get v) ∎
 
-sequenceV-cong : {S : Setoid ℓ₀ ℓ₀} {n : ℕ} {m₁ m₂ : Setoid.Carrier (VecISetoid (MaybeSetoid S) at n)} → VecISetoid (MaybeSetoid S) at _ ∋ m₁ ≈ m₂ → MaybeSetoid (VecISetoid S at n) ∋ sequenceV m₁ ≈ sequenceV m₂
-sequenceV-cong {S}                                       VecEq.[]-cong = Setoid.refl (MaybeSetoid (VecISetoid S at _))
-sequenceV-cong {S} {m₁ = just x ∷ xs} {m₂ = just y ∷ ys} (VecEq._∷-cong_ (just x≈y) xs≈ys) with sequenceV xs | sequenceV ys | sequenceV-cong xs≈ys
-sequenceV-cong {S} {m₁ = just x ∷ xs} {m₂ = just y ∷ ys} (VecEq._∷-cong_ (just x≈y) xs≈ys) | just sxs | just sys | just p = MaybeEq.just (VecEq._∷-cong_ x≈y p)
-sequenceV-cong {S} {m₁ = just x ∷ xs} {m₂ = just y ∷ ys} (VecEq._∷-cong_ (just x≈y) xs≈ys) | nothing | just sys | ()
-sequenceV-cong {S} {m₁ = just x ∷ xs} {m₂ = just y ∷ ys} (VecEq._∷-cong_ (just x≈y) xs≈ys) | just sxs | nothing | ()
-sequenceV-cong {S} {m₁ = just x ∷ xs} {m₂ = just y ∷ ys} (VecEq._∷-cong_ (just x≈y) xs≈ys) | nothing | nothing | nothing = Setoid.refl (MaybeSetoid (VecISetoid S at _))
-sequenceV-cong {S}                                       (VecEq._∷-cong_ nothing xs≈ys) = Setoid.refl (MaybeSetoid (VecISetoid S at _))
+sequenceV-cong : (S : Setoid ℓ₀ ℓ₀) {n : ℕ} {m₁ m₂ : Setoid.Carrier (VecISetoid (MaybeSetoid S) at n)} → VecISetoid (MaybeSetoid S) at _ ∋ m₁ ≈ m₂ → MaybeSetoid (VecISetoid S at n) ∋ sequenceV m₁ ≈ sequenceV m₂
+sequenceV-cong S                                       VecEq.[]-cong = Setoid.refl (MaybeSetoid (VecISetoid S at _))
+sequenceV-cong S {m₁ = just x ∷ xs} {m₂ = just y ∷ ys} (VecEq._∷-cong_ (just x≈y) xs≈ys) with sequenceV xs | sequenceV ys | sequenceV-cong S xs≈ys
+sequenceV-cong S {m₁ = just x ∷ xs} {m₂ = just y ∷ ys} (VecEq._∷-cong_ (just x≈y) xs≈ys) | just sxs | just sys | just p = MaybeEq.just (VecEq._∷-cong_ x≈y p)
+sequenceV-cong S {m₁ = just x ∷ xs} {m₂ = just y ∷ ys} (VecEq._∷-cong_ (just x≈y) xs≈ys) | nothing | just sys | ()
+sequenceV-cong S {m₁ = just x ∷ xs} {m₂ = just y ∷ ys} (VecEq._∷-cong_ (just x≈y) xs≈ys) | just sxs | nothing | ()
+sequenceV-cong S {m₁ = just x ∷ xs} {m₂ = just y ∷ ys} (VecEq._∷-cong_ (just x≈y) xs≈ys) | nothing | nothing | nothing = Setoid.refl (MaybeSetoid (VecISetoid S at _))
+sequenceV-cong S                                       (VecEq._∷-cong_ nothing xs≈ys) = Setoid.refl (MaybeSetoid (VecISetoid S at _))
 
 sequence-cong : {S : Set} {C : Set → S → Set} → (ShapeT : Shaped S C) → (α : Setoid ℓ₀ ℓ₀) → {s : S} {x y : C (Maybe (Setoid.Carrier α)) s} → ShapedISetoid (P.setoid S) ShapeT (MaybeSetoid α) at _ ∋ x ≈ y → MaybeSetoid (ShapedISetoid (P.setoid S) ShapeT α at _) ∋ Shaped.sequence ShapeT x ≈ Shaped.sequence ShapeT y
 
 sequence-cong : {S : Set} {C : Set → S → Set} → (ShapeT : Shaped S C) → (α : Setoid ℓ₀ ℓ₀) → {s : S} {x y : C (Maybe (Setoid.Carrier α)) s} → ShapedISetoid (P.setoid S) ShapeT (MaybeSetoid α) at _ ∋ x ≈ y → MaybeSetoid (ShapedISetoid (P.setoid S) ShapeT α at _) ∋ Shaped.sequence ShapeT x ≈ Shaped.sequence ShapeT y
-sequence-cong ShapeT α {x = x} {y = y} (shape≈ , content≈) with sequenceV (Shaped.content ShapeT x) | sequenceV (Shaped.content ShapeT y) | sequenceV-cong content≈
+sequence-cong ShapeT α {x = x} {y = y} (shape≈ , content≈) with sequenceV (Shaped.content ShapeT x) | sequenceV (Shaped.content ShapeT y) | sequenceV-cong α content≈
 sequence-cong ShapeT α {s} (shape≈ , content≈) | .(just x) | .(just y) | just {x} {y} x≈y = just (P.refl , (begin
   content (fill s x)
     ≡⟨ fill-content s x ⟩
 sequence-cong ShapeT α {s} (shape≈ , content≈) | .(just x) | .(just y) | just {x} {y} x≈y = just (P.refl , (begin
   content (fill s x)
     ≡⟨ fill-content s x ⟩